The Significance Of The ‘Ten Fundamentals’(Al-Mabādi’al-‘Asharah)In Conceptualizing The Epistemic Aims Of Learning In Islam - Muhammad Mustaqim Mohd.Zarif (Department of Usuluddin, University of Malaya, 2024)
Indexed by WOS/SCOPUS/MYCITE